77. Effect of sensory tricks on brain excitability in cervical dystonia: Sensory afferent inhibition study. Issue 1 (January 2015) - Butera, C.; Bianchi, F.; Amadio, S.; Taliano, G.; Urban, I.P.; Guerriero, R.; Cursi, M.; Comi, G.; Del Carro, U.
<x xml:space="preserve">Abstract</x> Sensory trick (ST), i.e. the improvement of dystonic posture by application of a sensory stimulus, is a typical Cervical Dystonia (CD) feature. Though its exact mechanism is still unknown, cortical sensorimotor integration processes are likely to be involved. Short latency afferent inhibition (SAI), the physiological inhibition of motor evoked potentials (MEP) mediated by somatosensory stimulation, could potentially help to understand this phenomenon. We evaluated by means of SAI whether the inhibitory effect of somatosensory afferent volley is preserved in CD patients; Moreover, we assessed if sensory trick may change SAI profile in patients with CD. We performed SAI at rest and during ST performance in 2 groups of CD patients: group 1 (n = 13), patients high-responsive to ST and group 2 (n = 8), patients no- or slightly responsive to ST. Results: We found an overall SAI impairment in both CD groups at rest; rather unexpectedly, SAI was less effective and MEP amplitude increased with ST in group 1, while just slight or no effect was observed in group 2. The physiological inhibition of sensory stimuli over motor cortex, measured with SAI, is decreased in our CD patients. The trick-related dystonia relief seems to occur through a paradoxical enhancement of the sensorimotor circuitry, at least in high-responsive ST patients.